Bisphosphonates attenuate age‐related muscle decline in Caenorhabditis elegans - Luke Slade; Shelby E. Bollen; Joseph J. Bass; Bethan E. Phillips; Kenneth Smith; Daniel J. Wilkinson; Nathaniel J. Szewczyk; Philip J. Atherton; Timothy Etheridge (Wiley, 2023)
Abstract Background Age‐related muscle decline (sarcopenia) associates with numerous health risk factors and poor quality of life. Drugs that counter sarcopenia without harmful side effects are lacking, and repurposing existing pharmaceuticals could expedite realistic clinical options. Recent studies suggest bisphosphonates promote muscle health; however, the efficacy of bisphosphonates as an anti‐sarcopenic therapy is currently unclear. Methods Using Caenorhabditis elegans as a sarcopenia model, we treated animals with 100 nM, 1, 10, 100 and 500 μM zoledronic acid (ZA) and assessed lifespan and healthspan (movement rates) using a microfluidic chip device. The effects of ZA on sarcopenia were examined using GFP‐tagged myofibres or mitochondria at days 0, 4 and 6 post‐adulthood. Mechanisms of ZA‐mediated healthspan extension were determined using combined ZA and targeted RNAi gene knockdown across the life‐course. Results We found 100 nM and 1 μM ZA increased lifespan (P < 0.001) and healthspan [954 ± 53 (100 nM) and 963 ± 48 (1 μM) vs. 834 ± 59% (untreated) population activity AUC, P < 0.05]. 10 μM ZA shortened lifespan (P < 0.0001) but not healthspan (758.9 ± 37 vs. 834 ± 59, P > 0.05), whereas 100 and 500 μM ZA were larval lethal. ZA (1 μM) significantly improved myofibrillar structure on days 4 and 6 post‐adulthood (83 and 71% well‐organized myofibres, respectively, vs. 56 and 34% controls, P < 0.0001) and increased well‐networked mitochondria at day 6 (47 vs. 16% in controls, P < 0.01). Genes required for ZA‐mediated healthspan extension included fdps‐1/FDPS‐1 (278 ± 9 vs. 894 ± 17% population activity AUC in knockdown + 1 μM ZA vs. untreated controls, respectively, P < 0.0001), daf‐16/FOXO (680 ± 16 vs. 894 ± 17%, P < 0.01) and agxt‐2/BAIBA (531 ± 23 vs. 552 ± 8%, P > 0.05). Life/healthspan was extended through knockdown of igdb‐1/FNDC5 (635 ± 10 vs. 523 ± 10% population activity AUC in gene knockdown vs. untreated controls, P < 0.01) and sir‐2.3/SIRT‐4 (586 ± 10 vs. 523 ± 10%, P < 0.05), with no synergistic improvements in ZA co‐treatment vs. knockdown alone [651 ± 12 vs. 635 ± 10% (igdb‐1/FNDC5) and 583 ± 9 vs. 586 ± 10% (sir‐2.3/SIRT‐4), both P > 0.05]. Conversely, let‐756/FGF21 and sir‐2.2/SIRT‐4 were dispensable for ZA‐induced healthspan [630 ± 6 vs. 523 ± 10% population activity AUC in knockdown + 1 μM ZA vs. untreated controls, P < 0.01 (let‐756/FGF21) and 568 ± 9 vs. 523 ± 10%, P < 0.05 (sir‐2.2/SIRT‐4)]. Conclusions Despite lacking an endoskeleton, ZA delays Caenorhabditis elegans sarcopenia, which translates to improved neuromuscular function across the life course. Bisphosphonates might, therefore, be an immediately exploitable anti‐sarcopenia therapy.